Cheese whey management: a review - Prazeres, Ana (2012)
Cheese whey is simultaneously an effluent with nutritional value and a strong organic and saline content. Cheese whey management has been focused in the development of biological treatments without valorization; biological treatments with valorization; physicochemical treatments and direct land application. In the first case, aerobic digestion is reported. In the second case, six main processes are described in the literature: anaerobic digestion, lactose hydrolysis, fermentation to ethanol, hydrogen or lactic acid and direct production of electricity through microbial fuel cells. Thermal and isoelectric precipitation, thermocalcic precipitation, coagulation/flocculation, acid precipitation, electrochemical and membrane technologies have been considered as possible and attractive physicochemical processes to valorize or treat cheese whey. The direct land application is a common and longstanding practice, although some precautions are required. In this review, these different solutions are analyzed. The paper describes the main reactors used, the influence of the main operating variables, the microorganisms or reagents employed and the characterizations of the final effluent principally in terms of chemical oxygen demand. In addition, the experimental conditions and the main results reported in the literature are compiled. Finally, the comparison between the different treatment alternatives and the presentation of potential treatment lines are postulated.